Research Progress on the Surface of High-Nickel Nickel–Cobalt–Manganese Ternary Cathode Materials: A Mini Review - Song, Liubin; Du, Jinlian; Xiao, Zhongliang; Jiang, Peng; Cao, Zhong; Zhu, Huali (Frontiers in Chemistry, 2020)
To address increasingly prominent energy problems, lithium-ion batteries have been widely developed. The high-nickel type nickel–cobalt–manganese (NCM) ternary cathode material has attracted attention because of its high energy density, but it has problems such as cation mixing. To address these issues, it is necessary to start from the surface and interface of the positive electrode material, explore the mechanism underlying the material’s structural change and the occurrence of side reactions, and propose corresponding optimization schemes. This article reviews the defects caused by cation mixing and energy bands in high-nickel NCM ternary cathode materials. This review discusses the reasons why the core-shell structure has become an optimized high-nickel ternary cathode material in recent years and the research progress of core-shell materials. The synthesis method of high-nickel NCM ternary cathode material is summarized. A good theoretical basis for future experimental exploration is provided.